Analysis of Project Construction Delay Using Fishbone Diagram at PT. Rekayasa Industri - Septiawan, Dimas Budi; Bekti, Rudy (Journal of Business and Management, 2016)
Abstract.This research focuses on finding the root problem of the construction delay that happened in several tasks at PT Rekayasa Industriâ€™s CGPX project. The project was planned to start on June 27th, 2011 and planned to be finished on April 8th, 2013. However, the actual project was finished almost one year later than the planned finished date (March 20th, 2014), despite the fact that the project started on time. The project delays will be analyzed through systematical methodology to find root cause that makes the project finished late using Ishikawa Diagram, then the result will be presented using â€œ5Mâ€ criteria. Finally, the best solution will be given as a feedback to the company to improve future project. The result shows that the most powerful delay is caused by human error. The recommendation given to the company is to increase the ability of workers to reduce the delays in these aspects. Way to increase the ability is by doing training, hire more professional person, recruit the third party, or give penalty if the drawing is late.Keyword: Project management, fishbone diagram, project delay, root cause analysisÂ